First characterization of aroma-active compounds in ripe Okrong mango Mangifera indica L. - Lertcharoenchaisakul, Piyakran; Phewpan, Apiniharn; Keeratipibul, Suwimon; Phuwapraisirisan, Preecha (Agriculture and Natural Resources, 2025)
Importance of the work: Okrong mango has a sweet taste and unique aroma but the active compounds contributing to such distinctive aroma remained uncharacterized. Objectives: To identify aroma-active compounds of ripe Okrong mangoes using a sensomics approach. Materials and Methods: Acceptability testand olfactory profile of Okrong mango were evaluated. Okrong mangoes were separately extracted by diethyl ether and dichloromethane, followed by SAFE to remove nonvolatile components. The aroma isolates concentrated by microdistillator were analyzed by GC-O/FID. Characterization of aroma-active compounds was performed by cAEDA, GC×GC-TOFMS and authentic samples. Results: Of mangoes evaluated, Okrong mango ranked the top in overall aroma and flavor. Okrong mango showed 8 attributes, namely caramel/sweet-like, fruity, sulfury, floral, terpeny, sweaty, coconut water and green in olfactory profile; in which the first three attributes received the highest scores. The mango extracted by diethyl ether expressed olfactory profile nearly identical to that of freshly cut mango. After the diethyl ether extract was analyzed by GC-O/FID and GC×GC-TOFMS, 43 aroma-active compounds with FD factors ranging from 4 to ≥2,048 were identified. Main finding: Forty-three aroma-active compounds with FD factors ranging from 4 to ≥2,048 were discovered. Two aroma-active compounds with FD factor ≥2,048, namely 4-methoxy-2,5-dimethyl-3(2H)-furanone (MDMF) and 4-hydroxy-2,5-dimethyl-3(2H)-furanone (HDMF), potentially contributed caramel-like aroma, which is distinguishing character of ripe Okrong mango.